Analysis of the effects of intersemiotic translation techniques on the poems from the book el Árbol del Bien y el Mal by Medardo Ángel Silva. - Rodríguez Abad, Indira Nastassja (2018)
Poetry is a complex art that is little understood and even less explored, that speaks with and through images, and whose real nuance is only truly grasped by peeling the different layers that make up the levels of the poetic meaning. That is why this project addresses the matter of translation of poetic texts focusing on the poems by Medardo Angel Silva using intersemiotic translation techniques. This project applies a mixed method approach including qualitative and quantitative analyses. Through the development of this research project the concepts of meaning, symbolism, image, semantic system and concept are revisited in order to establish a background for the study of the cognitive aspects of meaning and image, and how they play an important part in the conveyance of poetic messages. Once these concepts have been established in the literature review, this paper presents a new intersemiotic approach as a solution for poetry translation. The final part of the project is concerned with the practical application of the approach proposed on five subjects of study, which are evaluated under different parameters in order to assess the effectiveness of the intersemiotic approach to poetry translation. The results of the project are evidenced through observation guides and surveys, which are then presented in the form of statistical data with their respective analysis.